Local Government Social Intervention Strategy: A Sociological Study of the Effectiveness of Empowerment Programs - Asrijal, Andi; Indrawati, Ajeng R; Zulkifli, Zulkifli; Hasnawati, Hasnawati; Erdawati, Mega (Socious Journal, 2025)
Social inequality and economic disparity are still deep-rooted structural problems in the lives of Indonesian society. Although various empowerment programs have been launched by local governments, many of them are symbolic and technocratic, and fail to touch the roots of social injustice. This study aims to analyze social intervention strategies in community empowerment programs through a critical sociological approach. Using a literature study method with a qualitative approach, this study examines key theories such as power relations (Foucault), symbolic power (Bourdieu), capability approach (Sen and Nussbaum), and participatory parity (Fraser). The results of the analysis show that the dominance of power in the planning and implementation of empowerment programs often ignores the local socio-cultural context and narrows the space for citizen participation. Empowerment, which should be transformative, has instead become a tool for legitimizing elite, top-down policies. Therefore, the integration of substantive capability and participatory approaches in local policies is needed to dismantle structural inequality and build democratic, just, and inclusive governance. This study emphasizes the importance of reorienting the empowerment paradigm from merely administrative to social transformation that favors marginalized groups and expands the real freedom of society.